Incorporating small ensembles in the middle school band rehearsal to improve individual musical responsibility - Church, Byron (Kansas State University, 2024)
In my 7th grade band rehearsals, I found that my students were not covering parts as confidently as they are capable of, and sometimes hiding within their respective sections. By assigning each student a small ensemble and rehearsing them in a group setting, my project helped students develop their individual musicianship and raised confidence in their playing. To begin, I assigned each student in the band to a small ensemble, utilizing three different pieces from an ensemble methods book. Pieces were first rehearsed as larger ensembles, with the four groups on each different piece rehearsing simultaneously. As we progressed, parts were broken down for more detailed rehearsal, and ensembles were divided in half (two of the four at a time). Finally, the ensembles were separated, and students were on their own to start and play together. Over the course of my master’s program at Kansas State, I have shifted to a more peer-led and peer-centered approach to music education. I visualize this concept as horizontal versus vertical. In my beginning band (6th grade classes), I have continued to keep teaching from a teacher-centered (vertical) standpoint, ensuring that students are given proper instruction regarding technique, articulation, posture, etc. As my students move into 7th grade, instruction has turned more towards full-ensemble instruction to include blend, balance, intonation, etc. This remains as vertical teaching. During my master’s program, I have learned that this second year of band is a great time to have students do more horizontal learning and teaching as it gives them the chance to review their own playing while helping their fellow student. Another development in my teaching stems from some historically philosophical approaches to music education, namely diversifying students on different instruments and into different genres of music (and consequently music education). I have implemented both 7th and 8th grade jazz band into the school schedule. Like peer led (horizontal) teaching, the jazz program has offered students the opportunity to use their primary musical skills in another setting, be it on a secondary instrument, or through improvisation in the jazz ensembles. It also adds more opportunity for horizontal instruction; students on primary instruments in jazz helping students on secondary instruments in jazz. Before my time at Kansas State, I was more reserved in the idea of these young players adding a secondary instrument as they were just scratching the surface on their primary instruments. I have seen, through the addition of the jazz program, that though elements of the learning curve can initially be steep, students who seek a secondary instrument or at minimum a secondary genre have the potential to thrive on both. Building musical skills in one area also builds them in the other.
Keywords: Music; Band; Ensemble; Individual; Rehearsal; Education